An unusual case of severe asphyxia with the fetal position unexpectedly inverted in a malformed uterus: a case report - Jiro Abe; Takashi Nasu; Ayumu Noro; Junko Tsubaki (Journal of Medical Case Reports, 2024)
Abstract Background We present a severe neonatal consequence due to the unexpected and crucial inversion of the fetal position after sudden termination of tocolysis during early labor of a woman with congenital uterine anomaly. It has been reported that congenital uterine anomalies latently affect the fetal position. The clinical pitfalls in childbirth with uterine anomalies are discussed here on the basis of clinical evidence. Case presentation At a perinatal medical center in Japan, a 29-year-old Japanese mother who had a history of bicornuate uterus, received tocolysis to prolong her pregnancy for 5 days during the late preterm period after preterm-premature rupture of the membrane. She gave birth to a 2304 g male neonate of the gestational age of 35 weeks and 5 days with severe asphyxia by means of crash cesarean section for fetal sustained bradycardia after sudden termination of tocolysis. We found the fetal position to reverse from cephalic to breech position during early labor. He ended up having severe cerebral palsy after brain cooling against hypoxic-ischemic encephalopathy for 3 days. The mechanism of inversion from cephalic to breech position without amnionic fluid remains unclear, although women with a known diagnosis of a uterine anomaly have higher risk of adverse outcomes such as malpresentation. Conclusions When considering the clinical course of this case on the basis of the medical reports, we suspected that uterine anomalies and changes in intrauterine pressure could cause fetal malpresentation and adverse neonatal outcomes.